TGF-Beta Induced Key Genes of Osteogenic and Adipogenic Differentiation in Human Mesenchymal Stem Cells and MiRNA–mRNA Regulatory Networks - Du, Genfa; Cheng, Xinyuan; Zhang, Zhen; Han, Linjing; Wu, Keliang; Li, Yongjun; Lin, Xiaosheng (Frontiers in Genetics, 2021)
Background The clinical efficacy of osteoporosis therapy is unsatisfactory. However, there is currently no gold standard for the treatment of osteoporosis. Recent studies have shown that the switch from osteogenic to adipogenic differentiation of human bone marrow mesenchymal stem cells(hMSCs) induces osteoporosis. This study aimed to provide a more comprehensive understanding for biological mechanisms of this process, and identify key genes of osteogenic and adipogenic differentiation in hMSCs, to provide new insights for the prevention and treatment of osteoporosis. Methods We used microarray and bioinformatics approaches to obtain the differentially expressed genes (DEGs) of osteogenic and adipogenic differentiation, and we further analyzed the biological functions and pathways of these genes. Furthermore, the hub genes were identified and the miRNA-mRNA interaction networks of these hub genes were constructed. Results Our results showed that TGF-beta could promote osteogenic differentiation and inhibit adipogenic differentiation of hMSCs under an optimized microenvironment. According to our study, 98 upregulated genes involved in osteogenic differentiation and 66 downregulated genes involved in adipogenic differentiation were obtained,and the biological functions and pathways of these genes were analyzed. Based on the protein–protein interaction (PPI) networks,the hub genes (CTGF,IGF1,BMP2,MMP13,TGFB3,MMP3,SERPINE1) of the upregulated genes and the hub genes (PPARG,TIMP3,ANXA1,ADAMTS5,AGTR1,CXCL12,CEBPA) of the downregulated genes were identified,and statistical analysis revealed significant differences.In addition,36 miRNAs were screened among the upregulated hub genes, and 17 miRNAs were screened among the downregulated hub genes. Hub miRNAs (hsa-miR-27a/b-3p,hsa-miR-128-3p,hsa-miR-1-3p,hsa-miR-98-5p,hsa-miR-130b-3p) coregulated both osteogenic and adipogenic differentiation factors. Conclusion These upregulated hub genes in this study have been identified as potential targets for promotion of osteogenic differentiation in hMSCs;Whereas the downregulated hub genes could as potential targets for prevention of adipogenic differentiation. These hub miRNAs play an important role between adipogenesis and osteogenesis of hMSCs. These hub genes/miRNAs may not only be related to the prevention and treatment of osteoporosis, but also of obesity.